Values disclosures and trust in science: A replication study - Hicks, Daniel J.; Lobato, Emilio Jon Christopher (Frontiers in Communication, 2022)
While philosophers of science generally agree that social, political, and ethical values can play legitimate roles in science, there is active debate over whether scientists should disclosure such values in their public communications. This debate depends, in part, on empirical claims about whether values disclosures might undermine public trust in science. In a previous study, Elliott et al. used an online experiment to test this empirical claim. The current paper reports a replication attempt of their experiment. Comparing results of the original study and our replication, we do not find evidence for a transparency penalty or "shared values" effect, but do find evidence that the content of scientific conclusions (whether or not a chemical is found to cause harm) might effect perceived trustworthiness and that scientists who value public health and disclose this value might be perceived as more trustworthy.